Advancing ultrasound image analysis by capturing operator gaze patterns - Droste, R (2021)
Obstetric ultrasound scanning is a safe and effective tool for the early detection of fetal abnormalities and therefore crucial for determining the necessity of clinical intervention. However, ultrasound relies on operator expertise, which is a scarce resource globally. Moreover, there are large geographical and inter-observer variations of clinical outcomes. To address this, the PULSE project aims to develop a new generation of ultrasound scanning capabilities based on big data and machine learning models which capture the knowledge of experienced sonographers. To this end, the project team acquired a first-of-its-kind large-scale dataset of routine clinical ultrasound scanning with gaze-tracking data.